Education, formation, and learning: a reading of Mario Osorio Marques’ works (Revista Contexto & Educação, 2025)
This article aims to discuss the concepts of education and learning as processes of continuous and holistic formation in the work of Mario Osorio Marques, highlighting their implications for the field of education. Methodologically, it is an essay-based text within the field of philosophy of education, grounded in literature review and hermeneutic analysis. The study revealed that Marques’ work: revisits and reinterprets the concept of education as a holistic and continuous formative process of the human being, encompassing multiple dimensions of human existence and emphasizing openness to others, nature, and society; understands learning not as a mere adaptation to the existing reality or as the simple accumulation of knowledge and skills, but as a process of self-transcendent reconstruction of the human being and the structural components of the lifeworld - culture, society, and identity; demonstrates the necessity of a reconstructive hermeneutic exercise in education by its practitioners; emphasizes the role of schools and educational institutions in learning processes and in the formation of autonomous, responsible individuals capable of acting in a democratic society; and highlights Pedagogy as the science of education and educators.
Keywords: Education; Formation; Learning; Humanization; M. O. Marques